A Study of the Importance of Clonus Symptoms in Patients with Tramadol Poisoning - Fares Najari; Anahita Alizadeh-Ghamsari; Maryam Vahabzadeh; Bita Dadpour; Seyed Reza Mousavi; Ideh Baradaran Kayal (Journal of Toxicology)
Objectives. Clinical studies to reduce the side effects of tramadol, such as seizure, are necessary. Owing to the high prevalence of tramadol consumption and subsequent complications that result from seizures, the aim of the present study was to find a relationship between clonus and prediction of seizure outcome in patients with tramadol overdose. This can be used to determine the need for essential actions if a significant indicator of preventive medical measures is observed. Methods. In this case-control study, three groups of patients poisoned with tramadol and with marked ankle clonus were evaluated. A sample size of 50 patients per group was calculated using the Cohen first method. The data were analyzed using SPSS16 software. Results. All patients with ankle clonus were evaluated. Seizures occurred most commonly in patients aged 21–25 years or younger. The patients who received the preventive medication of magnesium sulfate were seizure-free for 72 h after admission. Conclusion. It is recommended that, for all patients referred with tramadol poisoning who have symptoms of ankle clonus, the administration of magnesium sulfate should be considered in addition to medication for the prevention of seizures and arrhythmias.